1999
DOI: 10.1021/jp983750s
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Methanol and Methoxy Groups Adsorbed on Powdered TiO2

Abstract: The photochemistry of CH3OH(a) and CH3O(a) adsorbed on TiO2 and the effect of O2 have been studied by infrared spectroscopy and mass spectrometry. In the absence of O2, CH3OH(a) desorbs molecularly, while CH3O(a) decomposes to form CH2O(g) under UV irradiation. The rate of CH3O(a) decomposition reaches maximum in the initial stage of UV irradiation and then decreases significantly. On the other hand, for the reaction in O2, the behavior of CH3O(a) depletion upon UV irradiation is very different, giving rise to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 24 publications
14
74
0
Order By: Relevance
“…(Molecular methanol exhibits as(CH3) and sym(CH3) vibrations at 2954 and 2849 cm −1 , respectively. These vibrational modes of adsorbed methoxy groups are seen at 2930 and 2815 cm −1 , in agreement with prior studies on methanol/TiO 2 systems [28][29][30].) The IR spectrum (bright green) after 1 min of UV irradiation shows dramatic changes: very large drops in the intensities of both molecularly and dissociatively adsorbed methanol, accompanied by the appearances of intense IR features characteristic of surface-bound formate species ( C H(HCOO) at 2872 cm −1 , and C O at 1546 cm −1 , sym(COO) at 1360 cm −1 , ␦ C H at 1379 cm −1 ).…”
Section: Photo-oxidation Of 2-butanone Methanol and Acetic Acidsupporting
confidence: 91%
“…(Molecular methanol exhibits as(CH3) and sym(CH3) vibrations at 2954 and 2849 cm −1 , respectively. These vibrational modes of adsorbed methoxy groups are seen at 2930 and 2815 cm −1 , in agreement with prior studies on methanol/TiO 2 systems [28][29][30].) The IR spectrum (bright green) after 1 min of UV irradiation shows dramatic changes: very large drops in the intensities of both molecularly and dissociatively adsorbed methanol, accompanied by the appearances of intense IR features characteristic of surface-bound formate species ( C H(HCOO) at 2872 cm −1 , and C O at 1546 cm −1 , sym(COO) at 1360 cm −1 , ␦ C H at 1379 cm −1 ).…”
Section: Photo-oxidation Of 2-butanone Methanol and Acetic Acidsupporting
confidence: 91%
“…2a) indicates that the β-carbon in MF oxidized to CO 2 through at least one intermediate. Using FTIR spectroscopy, Chuang et al [15] reported that methoxy formed CO 2 through formaldehyde and formate intermediates during methanol PCO, in agreement with Busca [16].…”
Section: Methyl Formate Reaction Pathwaymentioning
confidence: 58%
“…Collecting spectra after various irradiation times monitored the progression of PCO and provided qualitative information about the surface reaction. Previous band assignments and characteristic regions of functional groups [13][14][15]19,33,34], in conjunction with isotope shifts, identified absorption bands of surface species. Fig.…”
Section: Transient Photocatalytic Oxidation With Driftsmentioning
confidence: 99%
“…This rate was determined by using the real content of gold on the surface of the modes of molecularly adsorbed methanol [32][33][34][35]; and at 2922 and 2818 cm -1 , assigned to the same vibration modes of methoxy species bonded to TiO 2 [32][33][34][35]. In fact, various forms of surface methoxy species bonded to Ti 4+ sites are identified during the experiments, as evidenced by spectra at the region between 1600 and 950 cm -1 ( Figure 5).…”
Section: Methanol Carbonylation Catalyzed By Tio 2 -Supported Gold Samentioning
confidence: 97%
“…The bands at 1142 and 1119 cm -1 ( Figure 5) can be assigned to the -CH 3 rocking ( CH3 ) and the O-C stretching ( OC ) vibration modes of linear methoxy species bonded to Ti 4+ sites, respectively [34,35]. The band at 1438 cm -1 ( Figure 5) is assigned to the -CH 3 bending ( CH3 ) mode of methoxy species [34,36] and the band at 1037 cm -1 can be assigned to the  CO vibrations of doubly-bonded methoxy species on Ti 4+ sites [34].…”
Section: Methanol Carbonylation Catalyzed By Tio 2 -Supported Gold Samentioning
confidence: 99%